Companions, playmates and status-symbols: pet-keeping in Medieval England - Urmson, Ceri Jade (2016)
This dissertation examines archaeological evidence for pet keeping in Britain from the mid-1st Century AD until the 15th Century AD, to investigate past relationships between people and their pets. This thesis focusses on the presence of certain species (rabbits, squirrels) on archaeological sites and compile a spreadsheet with the data gathered, including sex, age, associated deposits and any visible pathologies. Both recent academic work and the documentary evidence show that pet keeping was more popular among children and women, and in the Middle Ages, both male and female members of the clergy; therefore this would suggest that pets are more likely to be present at sites frequented by these social subgroups, e.g. urban and ecclesiastical sites. This thesis will also discuss if the inclusion of pets in their owner’s grave would be archaeologically recognisable, and if not then why this would be the case. It also aims to address how common this practise was during the time stretching between the Iron Age to the end of the Middle Ages, and if there are any potential British examples of pet/human burials from this time period.